Opportunities and challenges of active immunotherapy in dogs with B-cell lymphoma: a 5-year experience in two veterinary oncology centers. Issue 1 (7th June 2019) - Marconato, Laura; Aresu, Luca; Stefanello, Damiano; Comazzi, Stefano; Martini, Valeria; Ferrari, Roberta; Riondato, Fulvio; Rouquet, Nicole; Frayssinet, Patrick; Sabattini, Silvia
Abstract : Background: Pet dogs spontaneously develop lymphoma. An anthracycline-based multidrug chemotherapy regimen represents the treatment cornerstone; however, cure is rarely achieved. We have been treating dogs with B-cell lymphoma with an autologous vaccine (APAVAC®) and CHOP-based chemotherapy since 2011. Methods: To better characterize the safety and efficacy of APAVAC®, and to find the best candidates for immunotherapy, we designed a retrospective study on all dogs treated with chemo-immunotherapy to date and compared them with those dogs treated with chemotherapy only. All dogs were completely staged and re-staged at the end of treatment. The primary endpoint was the effectiveness of chemo-immunotherapy, measured as time to progression (TTP), lymphoma-specific survival (LSS), and 1-, 2-, and 3-year survival rates. The secondary objective was safety. Results: Three hundred dogs were included: 148 (49.3%) received chemotherapy and 152 (50.7%) chemo-immunotherapy. Overall, the latter survived significantly longer (median LSS, 401 vs 220; P  <  0.001). Among dogs with diffuse large B-cell lymphoma, the 1-, 2- and 3-year survival rates were 20, 13 and 8% for chemotherapy, and 51, 19 and 10% for chemo-immunotherapy. The benefit of chemo-immunotherapy was particularly relevant in dogs with concurrent high serum LDH, stage V, substage a disease and not previously treated with steroids (median LSS, 480 vs 85 days; P  <  0.001). Among dogs with nodal marginal zone lymphoma, those having at least 3 of the aforementioned characteristics significantly benefited from chemo-immunotherapy (median LSS, 680 vs 160 days, P  <  0.001). The 1-, 2- and 3-year survival rates were 30, 16 and 10% for chemotherapy, and 55, 28 and 10% for chemo-immunotherapy. Among dogs with follicular lymphoma, lack of immunotherapy administration was the only variable significantly associated with increased risk of tumor-related death. Chemo-immunotherapy was remarkably well tolerated, with no local or systemic adverse events. Conclusions: Overall, the addition of immunotherapy to a traditional CHOP protocol is associated with improved outcome in dogs with B-cell lymphoma, regardless of histotype and evaluated prognostic factors. Moreover, the identikit of the best candidate for immune-therapy was delineated for the most common histotypes. The study also confirms the excellent tolerability of the vaccine.